A robust and self-healing elastomer achieved by a thio-β-diketone-Cu(ii) coordination and H-bonding dual crosslinked system. (1st June 2022) - An, Xiaoming; Liu, Jie; Zhang, Jia-Han; Huang, Xinxin; Zhu, Tangsong; Yan, Hongping; Jia, Xudong; Zhang, Qiuhong
Abstract : We report a novel elastomer possessing high stretchability, elasticity and self-healing ability, achieved by thio-β-diketone-Cu(ii ) coordination and H-bonding dual crosslinking. Flexible sensors are fabricated based on the elastomer. Abstract : Elastomers possessing good mechanical strength and self-healing capability are showing great importance in stretchable electronics, since they can play the role of robust substrates for devices, and prolong the service life of devices. However, it is hard to balance the trade-off between the high mechanical strength and self-healing ability. Here we propose the synergetic strategy via combining thio-β-diketone-Cu 2+ metal–ligand (M–L) coordination with hydrogen bonds in one system, through which high mechanical strength, good elasticity and self-healing ability are achieved. The elastomer displays excellent mechanical performances (with a fracture strength of 4.35 MPa and a fracture strain of 3400%). Meanwhile, the elastomer can realize a high self-healing efficiency (94%) within only 3 hours at 80 °C. X-ray absorption fine structure (XAFS) analysis demonstrates the reconfiguration of M–L coordination at the molecular level, and small angle X-ray scattering (SAXS) during stretching demonstrates the microphase structure change of the polymer at the nanoscale level. Based on the elastomer, a self-healable pressure sensor and a self-healable strain sensor are fabricated.